2018
DOI: 10.3389/fimmu.2018.00209
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro-Generated Tc17 Cells Present a Memory Phenotype and Serve As a Reservoir of Tc1 Cells In Vivo

Abstract: Memory CD8+ T cells are ideal candidates for cancer immunotherapy because they can mediate long-term protection against tumors. However, the therapeutic potential of different in vitro-generated CD8+ T cell effector subsets to persist and become memory cells has not been fully characterized. Type 1 CD8+ T (Tc1) cells produce interferon-γ and are endowed with high cytotoxic capacity, whereas IL-17-producing CD8+ T (Tc17) cells are less cytotoxic but display enhanced self-renewal capacity. We sought to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…However, Tc17 cells lacked significant expression of other cytolytic machinery (perforin and LAMP-1). Most studies to date in both mice and humans have shown that Tc17 cells lack cytolytic function (29,31,46,47), although some evidence for cytotoxic function has been reported (24,48). An interesting alternative interpretation of our data is that the secretion of granzymes is not cytolytic but leads to extracellular matrix degradation or promotion of inflammation (49,50).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, Tc17 cells lacked significant expression of other cytolytic machinery (perforin and LAMP-1). Most studies to date in both mice and humans have shown that Tc17 cells lack cytolytic function (29,31,46,47), although some evidence for cytotoxic function has been reported (24,48). An interesting alternative interpretation of our data is that the secretion of granzymes is not cytolytic but leads to extracellular matrix degradation or promotion of inflammation (49,50).…”
Section: Discussionmentioning
confidence: 60%
“…A possible explanation for these findings is that synovial Tc17 and Tc1 cells may have shared ancestry, which raises the question of plasticity between these subsets. Adoptive transfer of in vitro generated Tc17 cells into recipient mice showed that Tc17 cells can switch to an IL‐17A–negative Tc1 profile . A direct demonstration of this phenomenon came from an elegant IL‐17A fate‐mapping study using reporter donor IL‐17 Cre Rosa26 eYFP .…”
Section: Discussionmentioning
confidence: 99%
“…30 Tc17 cells are highly plastic in nature and can switch to interferon-γ producing Tc1 cells in certain tissues. 31 Entheseal CD4+ and CD8+ T cells are transcriptionally, phenotypically and functionally distinct from matched recirculating peripheral T cells. Entheseal T cells also have higher expression of transcripts involved in repair and tissue homeostasis, such as IL-10, TGFβ1 and VEGF-A when compared with their blood counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…T cells can be divided into CD4 + and CD8 + subsets, each possessing protective capabilities in the absence of the other during infection with C. neoformans (251)(252)(253)(254)(255). T cell-mediated immunity represents the most widely accepted potent host defense against C. neoformans infections, as well as the deepest downfall when a host is lymphopenic such as in HIV/AIDS patients.…”
Section: T Lymphocytesmentioning
confidence: 99%